Structural Disorder of Folded Proteins: Isotope-Edited 2D IR Spectroscopy and Markov State Modeling - Baiz, Carlos R. (Biophys J, 2015)
The conformational heterogeneity of the N-terminal domain of the ribosomal protein L9 (NTL9(1-39)) in its folded state is investigated using isotope-edited two-dimensional infrared spectroscopy. Backbone carbonyls are isotope-labeled ((13)C=(18)O) at five selected positions (V3, V9, V9G13, G16, and G24) to provide a set of localized spectroscopic probes of the structure and solvent exposure at these positions. Structural interpretation of the amide I line shapes is enabled by spectral simulations carried out on structures extracted from a recent Markov state model. The V3 label spectrum indicates that the β-sheet contacts between strands I and II are well folded with minimal disorder. The V9 and V9G13 label spectra, which directly probe the hydrogen-bond contacts across the β-turn, show significant disorder, indicating that molecular dynamics simulations tend to overstabilize ideally folded β-turn structures in NTL9(1-39). In addition, G24-label spectra provide evidence for a partially disordered α-helix backbone that participates in hydrogen bonding with the surrounding water.